Initiation of labor analgesia with injection of local anesthetic through the epidural needle compared to the catheter - Ristev G (Journal of Pain Research, 2017)
Goran Ristev,1 Angela C Sipes,1 Bryan Mahoney,2 Jonathan Lipps,1 Gary Chan,3 John C Coffman1 1Department of Anesthesiology, The Ohio State University Wexner Medical Center, Columbus, OH, USA; 2Department of Anesthesiology, Mount Sinai St. Luke’s and Mount Sinai Roosevelt, New York, NY, USA; 3Department of Anesthesiology, Perioperative & Pain Medicine, Icahn School of Medicine at Mount Sinai, New York, NY, USA Background: The rationale for injection of epidural medications through the needle is to promote sooner onset of pain relief relative to dosing through the epidural catheter given that needle injection can be performed immediately after successful location of the epidural space. Some evidence indicates that dosing medications through the epidural needle results in faster onset and improved quality of epidural anesthesia compared to dosing through the catheter, though these dosing techniques have not been compared in laboring women. This investigation was performed to determine whether dosing medication through the epidural needle improves the quality of analgesia, level of sensory blockade, or onset of pain relief measured from the time of epidural medication injection. Methods: In this double-blinded prospective investigation, healthy term laboring women (n=60) received labor epidural placement upon request. Epidural analgesia was initiated according to the assigned randomization group: 10 mL loading dose (0.125% bupivacaine with fentanyl 2 µg/mL) through either the epidural needle or the catheter, given in 5 mL increments spaced 2 minutes apart. Verbal rating scale (VRS) pain scores (0–10) and pinprick sensory levels were documented to determine the rates of analgesic and sensory blockade onset. Results: No significant differences were observed in onset of analgesia or sensory blockade from the time of injection between study groups. The estimated difference in the rate of pain relief (VRS/minute) was 0.04 (95% CI: −0.01 to 0.11; p=0.109), and the estimated difference in onset of sensory blockade (sensory level/minute) was 0.63 (95% CI: −0.02 to 0.15; p=0.166). The time to VRS ≤3 and level of sensory block 20 minutes after dosing were also similar between groups. No differences in patient satisfaction, or maternal or fetal complications were observed. Conclusion: This investigation observed that epidural needle and catheter injection of medications result in similar onset of analgesia and sensory blockade, quality of labor analgesia, patient satisfaction, and complication rates. Keywords: labor analgesia, epidural needle, epidural catheter, analgesic onset